Thermal expansion properties of stannosilicate molecular sieve with MFI type structure - Niphadkar, P. S.; Bhange, Deu S.; Selvaraj, K.; Joshi, P. N. (Chemical Physics Letters, 2012)
An in situ high temperature X-ray diffraction study was carried out for investigating the thermal expansion properties of Si-MFI and SnSi-MFI molecular sieves. The thermal stability up to 973 K and a negative lattice thermal expansion in anisotropic manner was exhibited by both the phases in the temperature range of 373-973 K. The trend observed in contraction along the axes was as: a > c > b. The substitution of Sn4+ in MFI framework resulted in an expansion of unit cell volume and in an increase in the lattice thermal expansion coefficient in the temperature range 423-973 K. (C) 2012 Elsevier B. V. All rights reserved.